Methylmercury levels in commonly consumed fish and methylmercury exposure of children and women of childbearing age in Hong Kong, a high fish consumption community - Chan, Peggy Hiu Ying; Chan, Michael Ho Ming; Li, Albert Martin; Cheung, Robert Chi Keung; Yu, Xin Ting; Lam, Hugh Simon (Environmental research, 2018)
Despite high fish consumption levels of Hong Kong residents, little is known about the MeHg exposure levels of Hong Kong high-risk populations (i.e. young children and women of childbearing age). To investigate the MeHg levels in fish commonly consumed in Hong Kong and assess the exposure levels of local kindergarten children and women of childbearing age. A community-based survey was conducted in randomly recruited local kindergartens. The MeHg concentrations of the most commonly consumed fish items were measured. Based on their fish consumption data, subjects’ MeHg exposure levels were estimated and compared with the reference dose (RfD) set by U.S. Environmental Protection Agency. A total of 2917 mother-child pairs were recruited. The MeHg levels of the fish samples ranged from < 2–1498.7 ng/g. Six frozen cod fish samples contained MeHg levels exceeding the local legal limit of 500 ng/g. The median estimated MeHg intake for children and mothers were 0.29 and 0.22 µg/kg bw/wk, respectively. Approximately 16% children and 9% mothers exceeded the RfD. Apart from frozen cod fish, most fish species commonly consumed in Hong Kong had low MeHg content. Although the majority of our subjects were exposed to low MeHg levels, high fish consumers could still exceed the RfD and are potentially at risk of MeHg toxicity. To avoid excessive MeHg exposure, we suggest that young children and their mothers may consume a variety of locally available fish, but avoid consumption of frozen cod fish. •Most fish commonly consumed by local high risk populations contain low MeHg levels.•Half of the examined cod fish contained MeHg levels exceeding the local legal limit.•16% children and 9% women are exposed to MeHg levels exceeding the reference dose.